Mouth opening in patients irradiated for head and neck cancer: A prospective repeated measures study. Issue 5 (May 2015) - Kamstra, J.I.; Dijkstra, P.U.; van Leeuwen, M.; Roodenburg, J.L.N.; Langendijk, J.A.
Summary: Objectives: Aims of this prospective cohort study were (1) to analyze the course of mouth opening up to 48 months post-radiotherapy (RT), (2) to assess risk factors predicting decrease in mouth opening, and (3) to develop a multivariable prediction model for change in mouth opening in a large sample of patients irradiated for head and neck cancer. Materials and methods: Mouth opening was measured prior to RT (baseline) and at 6, 12, 18, 24, 36, and 48 months post-RT. The primary outcome variable was mouth opening. Potential risk factors were entered into a linear mixed model analysis (manual backward-stepwise elimination) to create a multivariable prediction model. The interaction terms between time and risk factors that were significantly related to mouth opening were explored. Results: The study population consisted of 641 patients: 70.4% male, mean age at baseline 62.3 years (sd 12.5). Primary tumors were predominantly located in the oro- and nasopharynx (25.3%) and oral cavity (20.6%). Mean mouth opening at baseline was 38.7 mm (sd 10.8). Six months post-RT, mean mouth opening was smallest, 36.7 mm (sd 10.0). In the linear mixed model analysis, mouth opening was statistically predicted by the location of the tumor, natural logarithm of time post-RT in months (Ln (months)), gender, baseline mouth opening, and baseline age. All main effects interacted with Ln (months). Conclusion: The mean mouth opening decreased slightly over time. Mouth opening was predicted by tumor location, time, gender, baseline mouth opening, and age. The model can be used to predict mouth opening.